PARADIGMA PEMAHAMAN IMPLEMENTASI SISTEM MANAJEMEN MUTU PADA PELAYANAN PUBLIK - Desak N. Siksiawati; Siti Andriati Widartien; Lailatul Maghfiroh (UPT Penerbitan Universitas Jember)
Implementation of the quality management system to make the organization had to maintain quality standards in every aspect of the organization. Standard quality management system (QMS) that has grown and the right to public services is ISO 9001, the means of achieving quality objectives that are expected to respond to the challenges of globalization by increasing efficiency and effectiveness to satisfy stakeholders. This study aims to determine the implementation of the Quality Management System ISO 9001 in terms of aspects of documentation and its implementation from the aspect of management responsibility and alternative measures for the improvement of the implementation strategy. Locus research on public services in the Provincial Government of East Java. The method of analysis using primary and secondary data were then presented with a descriptive analysis of narrative. The results showed that the quality management system implementation of aspects of the documentation complies with the quality guidelines. However, the implementation of quality management systems in the aspect of management responsibilities have not been able to walk properly because the habit of